Numerical study and correlations for heat and mass transfer coefficients in indirect evaporative coolers with condensation based on orthogonal test and CFD approach. (June 2020) - Wan, Yangda; Soh, Alexander; Shao, Yunlin; Cui, Xin; Tang, Yongzhi; Chua, Kian Jon
Highlights: Developing of a CFD model specifically tailored to the IEC with condensation. Studying temperature and humidity ratio distributions inside an IEC. Conducting a single-factor analysis for nine factors to study respective effects. Conducting a multiple-factor analysis based on orthogonal test method. Proposing empirical correlations for mean heat and mass transfer coefficients. Abstract: Previous studies obtained the heat and mass transfer coefficients of Indirect evaporative coolers (IECs) with condensation based on the following assumptions: (1) empirical equations in the dry channel without water evaporation or condensation, or the boundary condition is assumed to be a constant surface heat flux or temperature so that constant values of Nusselt number can be employed for evaluating the heat transfer coefficient; and (2) Lewis number is assumed to be unity so that the mass transfer coefficients can be then calculated via the heat and mass transfer analogy. Thus far, the heat and mass transfer coefficients of IECs with condensation under naturally formed boundary condition are lacking. In this paper, an experimental-validated computational fluid dynamics (CFD) model has been established to investigate the heat and mass transfer processes of IECs incorporating the phenomenon of condensation. A single factor analysis and a multiple factor analysis are concurrently carried out to evaluate the effects of the nine parameters on the heat and mass transfer processes of IECs. Key findings revealed that both mean Nusselt and Sherwood numbers under the presented conditions are larger than those obtained under constant surface temperature and heat flux conditions; and the respective values of the primary and secondary Lewis numbers are observed to change from 0.37 to 0.75 and 0.70 to 0.85 which severely deviate from the conventional assumed value of unity. Finally, empirical correlations are developed for the mean heat and mass transfer coefficients based on an orthogonal test method. The simplified linear correlations can serve as new fundamental references to account for IEC that are consistently experiencing with condensation.